2013
DOI: 10.1074/jbc.m112.435917
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Inducible (Fn14)-specific Antibodies Concomitantly Display Signaling Pathway-specific Agonistic and Antagonistic Activity

Abstract: Background: Fn14 is a therapeutic target in various diseases. Results: Anti-Fn14 antibodies activate the alternative NFB pathway but not other Fn14-related activities induced by soluble or membrane-bound TWEAK. Fc␥R-bound anti-Fn14 antibodies, however, activate the full spectrum of Fn14-associated activities. Conclusion: Anti-Fn14 antibodies elicit agonistic activities differing from those of the natural Fn14 ligand TWEAK. Significance: These findings influence the rationale of designing Fn14-targeted therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 42 publications
(44 reference statements)
3
58
0
Order By: Relevance
“…Mimicking that function with a secondary antibody dramatically increased the level of cytokines released by enavatuzumab; this finding is consistent with increased functional activity of enavatuzumab and other TNFRSF agonist antibodies when crosslinked with a secondary antibody or Protein A (Chao et al, 2013;Salzmann et al, 2013;Chuntharapai et al, 2001;White et al, 2013;Li et al, 2006;Dhein et al, 1992;Chodorge et al, 2012). However, crosslinking the antibody did not increase ALT/AST release, which was only observed when immune cells were present.…”
Section: Discussionsupporting
confidence: 69%
“…Mimicking that function with a secondary antibody dramatically increased the level of cytokines released by enavatuzumab; this finding is consistent with increased functional activity of enavatuzumab and other TNFRSF agonist antibodies when crosslinked with a secondary antibody or Protein A (Chao et al, 2013;Salzmann et al, 2013;Chuntharapai et al, 2001;White et al, 2013;Li et al, 2006;Dhein et al, 1992;Chodorge et al, 2012). However, crosslinking the antibody did not increase ALT/AST release, which was only observed when immune cells were present.…”
Section: Discussionsupporting
confidence: 69%
“…To further test whether 4G5, 18D1, and 5B6 can acquire agonistic activity by interaction with Fc receptors, we analyzed co-cultures of HT1080 cells and HEK293 cells transiently expressing CD16, CD32A CD32B, and CD64 and analyzed anti-Fn14 antibodyinduced IL8 production. As observed before for PDL192 and P4A8, 7 all three llama-derived antibodies acted as strong agonists in the presence of Fcγ receptor expressing cells (Fig. 3D).…”
Section: Fn14-specific Igg1 Antibodies Become Strong Agonists Upon Olmentioning
confidence: 57%
“…Indeed, oligomerization with protein G or binding to FcγRs can achieve strong agonistic activity for various antibodies targeting members of the TNF receptor family. We have recently shown a similar behavior with P4A8 and PDL192 7 and, accordingly, all three Fn14-targeting llama antibodies displayed strong agonistic activity upon crosslinking with protein G and efficiently triggered interleukin-8 (IL8) production, cell death induction and enhancement of TNF-induced cell death ( Fig. 3A-C).…”
Section: Fn14-specific Igg1 Antibodies Become Strong Agonists Upon Olmentioning
confidence: 76%
See 1 more Smart Citation
“…Active RIPK3 phosphorylates the pseudokinase MLKL, leading to its oligomerisation and MLKL-mediated membrane permeabilisation. 20 Similar to SMs, TWEAK, a TNF superfamily ligand, can synergise with TNF to kill tumour cells, [21][22][23][24] and cells that are sensitive to TWEAK-induced death are also sensitive to SMs. 24 Earlier reports demonstrated that TWEAK not only synergises with cell death ligands such as TNF, TRAIL and Fas but also with interferon-γ (IFNγ) to kill cancer cells.…”
mentioning
confidence: 99%